RETRACTION NOTICE TO : A Simulated Annealing Heuristic For The Green Vehicle Routing Problem - Moch Yasin; Vincent F. Yu (Systemic: Information System and Informatics Journal, 2015)
[RETRACTED]. Retracted due to double publication / double submission with article in Proceedings of the Institute of Industrial Engineers Asian Conference 2013 pp 1261-1269. https://link.springer.com/chapter/10.1007/978-981-4451-98-7_149